Trends in Stable Isotopes and Climate Proxies From Late Changhsingian Ghost Landscapes of the Karoo Basin, South Africa - Gastaldo, Robert A.; Tabor, Neil J.; Neveling, Johann (Frontiers in Ecology and Evolution, 2020)
The stable carbon-and-oxygen isotope values from in situ pedogenic carbonate-cemented nodules and vertebrate apatite in the vertebrate assemblage zones of the Balfour Formation, Karoo Basin, South Africa, have been previously interpreted to show a unidirectional climate trend toward hyper-aridity. The Daptocephalus/Lystrosaurus boundary is considered by many authors as equivalent to the PTB in the basin. We have analyzed the stable carbon-and-oxygen isotopes of pedogenic carbonate nodules sampled from fourteen horizons of intraformational pedogenic nodular conglomerate at Old Lootsberg Pass to better understand the climate under which these vertebrate assemblages existed. Analysis of these refractory soil constituents provides insight into the climate under which these “ghost” soils formed, where no other physical record of their existence is found in the stratigraphy. A positive correlation exists between δ13C and δ18O values of micrite cements of carbonate nodules taken from a measured stratigraphic thickness of 200 m, which spans the biozone boundary as currently defined. Samples taken from the same lag deposit show similar and relatively narrow ranges of isotope values. Samples cluster into two isotopic groups. Values in the first cluster more tightly in all sampled nodules, and are interpreted to indicate that these originated from paleosols that formed under similar climate controls. Values from the second group display a wider analytical variance. These are interpreted to indicate that they originated under polygenetic soil-forming conditions representing the reworking of either: (1) more than one paleosol, the calcite-cemented nodules of which represent precipitation under both closed and open-system controls; or (2) one or more compound-composite paleosols. Stable-isotope trends based on PNCs analyzed, thus far, demonstrate an overall shift over time in the ghost landscapes. More seasonally dry soils formed under a climate that can be characterized as warm/dry accompanied by lower precipitation in the lower part of the section. In contrast, soils in the upper part of the section formed under cool and moist conditions, with increased precipitation near the biozone boundary. Hence, latest Permian climate associated with the more seasonally dry landscapes demonstrate a trend towards cooler and wetter conditions, which is opposite to the trend widely held in the literature.